Time-Dependent Alterations in Liver Oxidative Stress due to Ethanol and Acetaldehyde (Journal of Renal and Hepatic Disorders, 2022)
Binge drinking is a major public health issue and ethanol-related liver insult may play a major role in the pathology of alcoholic liver disease. However, the degree of oxidative stress, cell death and contribution of acetaldehyde to liver damage over a 24-h period has yet to be determined. Herein, we aimed to investigate the effect of acute alcohol and elevated acetaldehyde levels on hepatic oxidative damage, apoptosis, and antioxidant enzyme activity over a 24-h period. Male Wistar rats were divided into four groups and animals were pre-injected (intraperitonially [i.p.]) with either saline (0.15 mol/L) or cyanamide (5-mmol/kg body weight), followed by either saline (0.15 mol/L) or ethanol (75-mmol/kg bodyweight). After 2.5, 6 and 24 h, hepatic cytosolic and mitochondrial fractions were analysed for indices of oxidative stress. At 2.5 h, cytosolic glutathione and malondialdehyde levels were significantly reduced and increased, respectively, with alcohol treatment. Caspase-3 activity and cytochrome c levels were increased with alcohol treatment at 24 h. The combination of cyanamide and alcohol treatment at 24 h led to a significant increase in serum alanine aminotransferase levels, and reduced albumin and total protein levels. Furthermore, glutathione peroxidase activity and glutathione reductase activity were significantly decreased and increased, respectively. Finally, superoxide dismutase activity was decreased in cytosol and increased in the mitochondria after cyanamide and ethanol treatment, respectively. This study indicates a complex differential effect of alcohol and acetaldehyde, whereby alcohol toxicity in the mitochondria takes place throughout the 24-h period, but raised acetaldehyde has a further detrimental effect on liver function.
Keywords: acetaldehyde; alcohol; antioxidant; apoptosis; mitochondria; oxidative stress